Contrasting Effects of Long-Term Nitrogen Deposition on Plant Phosphorus in a Northern Boreal Forest - Palmqvist, Kristin; Nordin, Annika; Giesler, Reiner (Frontiers in Forests and Global Change, 2020)
Ecosystem responses of carbon and nitrogen (N) biogeochemistry to N deposition have a high variation across sites. Phosphorus (P), which can interact strongly with N, can be the cause of some of this variation. We quantified plant N and P concentrations and estimated P stocks in aboveground foliage, and soil O-horizon P concentrations and stocks after 18 years in a long-term stand-scale (0.1 ha) N addition experiment [12.5 kg (N1) and 50 kg (N2) N ha−1 year−1] in a c. 100-years-old boreal spruce [Picea abies (L.) Karst] forest. Basal area growth had increased by 65% in the N2 treatment compared to control, along with a higher leaf area index, and lower litter decomposition rates. The higher tree growth occurred during the initial c. 10-years period thereafter resuming to control rates. We hypothesized that increased plant demand for P together with decreased recycling of organic matter in this initially N limited system may have decreased plant-available P, with possible consequences for longer-term biogeochemistry and ecosystem production. However, resin-extractable P did not differ between the three treatments (0.32 kg P ha−1), and plant NP ratios and P concentrations and O-horizon P characteristics were similar in the N1 and control treatments. The N2 treatment doubled total P in the O-horizon (100 vs. 54 kg P ha−1), explained by an increase in organic P. The N concentration, NP ratio, and spruce needle biomass were higher in N2, while the P stock in current year needles was similar as in the control due to a lower P concentration. In addition to P dilution, increased light competition and/or premature aging may have caused the reduction of N-stimulated growth of the trees. For the dominant understory shrub [Vaccinium myrtillus (L.)] no changes in growth was apparent in N2 despite a significantly higher NP ratio compared to control (15 vs. 9, respectively). We therefore conclude that increased NP ratio of vegetation cannot be used as a sole indicator of P limitation. The vegetation and O-horizon changes in N2 were still large enough to merit further studies addressing whether such high N loads may alter ecosystem biogeochemistry toward P limitation. For the lower N addition rate, relevant from an anthropogenic N deposition perspective, we suggest it had no such effect.